2010
DOI: 10.1016/j.frl.2010.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Does the weather affect stock market volatility?

Abstract: Abstract. This paper investigates the empirical association between stock market volatility and investor mood-proxies related to the weather (cloudiness, temperature and precipitation) and the environment (nighttime length). Overall, our results suggest that cloudiness and length of nighttime are inversely related to historical, implied and realized measures of volatility. The strength of association seems to vary with the location of an exchange on Earth with respect to the equator. Weather deviations from se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(43 citation statements)
references
References 37 publications
4
38
0
1
Order By: Relevance
“…Cunningham (1979) showed that in both summer and winter, a clear day will create a good mood, with temperature having a negative (positive) association with mood in the summer (winter). Schwarz and Clore (1983) suggested that people would gain more satisfaction from a bright day than a gloomy day, while Symeonidis et al (2010) noted that cloud cover has often been regarded as a natural factor influencing mood. Page et al (2007) found that in England and Wales, temperature has a negative correlation with mood in the summer months; when the temperature is above 18°C, an increase of one degree was found to be associated with a 3.8% rise in suicide rates.…”
Section: Introductionmentioning
confidence: 99%
“…Cunningham (1979) showed that in both summer and winter, a clear day will create a good mood, with temperature having a negative (positive) association with mood in the summer (winter). Schwarz and Clore (1983) suggested that people would gain more satisfaction from a bright day than a gloomy day, while Symeonidis et al (2010) noted that cloud cover has often been regarded as a natural factor influencing mood. Page et al (2007) found that in England and Wales, temperature has a negative correlation with mood in the summer months; when the temperature is above 18°C, an increase of one degree was found to be associated with a 3.8% rise in suicide rates.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies including those by Baker and Stein (2004), Brown (1999), and Wright and Bower (1992) point out that weather conditions can change the risk preference of investors, valuation of financial assets, and trading willingness; thus, they have a significant influence on market volatility. Chang et al (2008), Lu and Chou (2012), and Symeonidis et al (2010) provide empirical evidence to support the argument that the weather effect can be better captured by volatility than stock returns. However, relatively few extant studies pay attention to the volatility behavior.…”
Section: Introductionmentioning
confidence: 71%
“…They finally suggest that market makers' behavior, rather than that of individual investors, accounts for the relation between the weather and the stock returns. Symeonidis et al (2010) empirically test the association between the stock volatilities and investors' behavior by using the index returns from 26 international stock exchanges and weather-(cloud cover, temperature, and precipitation) and environment-related (the length of night time) variables as proxies for investors' mood. They find that the historical, implied, and realized return volatilities are inversely related to cloudiness and the length of night time, though the results can vary according to the exchange location.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They attribute the differential reaction to widespread local media coverage of the disasters, which increases fear and anxiety among US investors and causes them to be more pessimistic about stock prices. Hirshleifer (2001), Baker and Wurgler (2006) and Symeonidis et al (2010) provide a review of the relevant literature.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%